Intrathecal immunoglobin synthesis and its role in patients with neurosyphilis - Huang, Xiyue; Ying, Shanshan; Luo, Lan; Li, Lixin; Li, Dongdong; Xie, Yi (Frontiers in Public Health, 2022)
Background Intrathecal protein synthesis (ITS) occurs in various central nervous system disorders, but few quantitative studies have focused on ITS for neurosyphilis (NS) in southwestern China. We made a study to quantitatively assess the ITS in patients with NS and to investigate the association between ITS and the stages of NS. Methods CSF–serum specimen pairs from 142 patients (66 NS and 76 non-NS/syphilis) were collected for routine CSF and serum tests. The NS group was divided into slight and severe subgroups according to the NS stages. Three formulas for the quantitative determination of the intrathecal synthesis were calculated to characterize the specimens, including the Ig index (QIg/Qalb), Ig extended index (Ig_EI), and intrathecally synthesized fraction (IgIF) using the hyperbolic function. The role of QTPPA/QIgG as an antibody index (AI = Q specific Ig/QIgG) was also explored. Results Sero_TRUST titres (1:16, 1:1-1:256), sero_TPPA titres (1:163840, 1:1280-1:1310720), total protein (MTP), and CSF_Igs (p < 0.05) were found to be significantly elevated in the NS group. Intrathecal Ig synthesis can be identified using all three formulas in the NS group. The pattern of Ig intrathecal synthesis was IgIF-G (48.62%) > IgIF-A = IgIF-M (p < 0.05), with the dominant intrathecal fraction being IgG (median, 48.62%), which was also verified by QIgG> Qalb> QIgM = QIgA. In the slight NS group, the intrathecal fractions of IgM (>0 in 4 out of 20 cases) and IgG (>0 in 16 out of 20) were lower than the intrathecal fractions of IgM (>0 in 19 out of 35 cases) and IgG (>0 in 33 out of 38) in the severe group (p < 0.05). The area under the curve (AUC) of the CSF_TPPA antibody index was 0.867 (0.792, 0.922), with an optimal cutoff point of 0.81, providing a sensitivity of 88.91% and specificity of 84.62%. Conclusion Although the intrathecal synthesis pattern is IgG dominant in patients with NS, brain-derived IgM and IgA can also be found. Moreover, intrathecal IgM and IgG were associated with a parenchymatous type of neurosyphilis. Syphilis-specific antibodies are a new potential tool for NS diagnosis.